How to implement live video recording in the clinical environment: A practical guide for clinical services. Issue 6 (19th May 2017) - Lloyd, Adam; Dewar, Alistair; Edgar, Simon; Caesar, Dave; Gowens, Paul; Clegg, Gareth
Abstract: Background: The use of video in healthcare is becoming more common, particularly in simulation and educational settings. However, video recording live episodes of clinical care is far less routine. Aim: To provide a practical guide for clinical services to embed live video recording. Materials and Methods: Using Kotter's 8‐step process for leading change, we provide a 'how to' guide to navigate the challenges required to implement a continuous video‐audit system based on our experience of video recording in our emergency department resuscitation rooms. Results: The most significant hurdles in installing continuous video audit in a busy clinical area involve change management rather than equipment. Clinicians are faced with considerable ethical, legal and data protection challenges which are the primary barriers for services that pursue video recording of patient care. Discussion: Existing accounts of video use rarely acknowledge the organisational and cultural dimensions that are key to the success of establishing a video system. This article outlines core implementation issues that need to be addressed if video is to become part of routine care delivery. Conclusion: By focussing on issues such as staff acceptability, departmental culture and organisational readiness, we provide a roadmap that can be pragmatically adapted by all clinical environments, locally and internationally, that seek to utilise video recording as an approach to improving clinical care.